The Level of Scientific Thinking Skills and Its Relationship to Achievement and Scientific Curiosity Among Eighth-Grade Basic Male Students in Science - Govan Sabah Abduljabar; Elham Ahmad Hamma (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The research aimed at identifying the relationship between scientific thinking skills level، achievement، and scientific curiosity among male students in eighth-grade basic in science. The researchers used the descriptive correlative method. The study population composed 0f (1409) male students at eighth-grade basic in Soran Education Directorate and affiliated to the general Directorate of Education in Erbil. the study sample consisted of (400) male students، randomly selected from (4) schools. for the academic year 2021/2022. To achieve the goals of the research ، the researchers prepared two study tools: scientific thinking skills test، scientific curiosity scale، and after conducting statistical analyzes، the major finding from this research were as follows: The level of scientific thinking skills and scientific curiosity among male students in eighth-grade basic is acceptable. There is a statistically significant correlation between the research variables among male students in eighth-grade basic in science.